2015
DOI: 10.1186/s12955-015-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the BRIGHTLIGHT Survey, a patient-reported experience measure for young people with cancer

Abstract: BackgroundPatient experience is increasingly used as an indicator of high quality care in addition to more traditional clinical end–points. Surveys are generally accepted as appropriate methodology to capture patient experience. No validated patient experience surveys exist specifically for adolescents and young adults (AYA) aged 13–24 years at diagnosis with cancer. This paper describes early work undertaken to develop and validate a descriptive patient experience survey for AYA with cancer that encompasses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 18 publications
1
58
0
Order By: Relevance
“…Empirical work started to emerge slowly, and early examples include the work of Hollis and Morgan (2001), Lewis, Fallon, van Dongen-Melman, and Barr (2002) and Kelly et al (2004). The scale of empirical research has grown in scope and ambition with the current Brightlight study exploring the benefits of specialist care for AYAs with cancer (Taylor et al, 2015). More recently, the James Lind Alliance (Aldiss et al, 2018) reported after a Priority Setting exercise exercise on the top ten AYA cancer research priorities that identified gaps and unanswered questions in research, the answers to which may reduce the individual and societal burden of young peoples' cancer.…”
Section: E X Ample S Of An Archive Of the De Velopment Of Aya A S Amentioning
confidence: 99%
“…Empirical work started to emerge slowly, and early examples include the work of Hollis and Morgan (2001), Lewis, Fallon, van Dongen-Melman, and Barr (2002) and Kelly et al (2004). The scale of empirical research has grown in scope and ambition with the current Brightlight study exploring the benefits of specialist care for AYAs with cancer (Taylor et al, 2015). More recently, the James Lind Alliance (Aldiss et al, 2018) reported after a Priority Setting exercise exercise on the top ten AYA cancer research priorities that identified gaps and unanswered questions in research, the answers to which may reduce the individual and societal burden of young peoples' cancer.…”
Section: E X Ample S Of An Archive Of the De Velopment Of Aya A S Amentioning
confidence: 99%
“…Our patient satisfaction survey had various weaknesses, particularly the fact that it was answered only by patients involved in the Youth Project activities, who were more likely to have a positive attitude to such initiatives. Far from being a comprehensive qualitative and quantitative survey on the quality of life and psychosocial needs of AYA, as undertaken by other authors, the questionnaire was simply a preliminary tool for collecting positive and negative comments from our patients and involving them in assessing the program. The questionnaire nonetheless revealed our patients’ favorable judgment, particularly as concerns relational aspects, and it further confirms the value of such projects.…”
Section: Discussionmentioning
confidence: 99%
“…This has the benefit of having built-in methods for checking errors and allows routing of questions, automatically eliminating irrelevant questions on the basis of previous answers. The survey instrument development has been described previously 23 ; the survey consists of 15 domains identified by young people as important in their cancer experience, including their experience before diagnosis. The survey questions were mainly read out by the interviewer and answered from a prespecified list, with options for including free text and dates where applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Information on symptoms experienced before the diagnosis of cancer was ascertained through yes-or-no responses to 16 specified symptoms (patients could respond yes to >1 symptoms), with any other symptoms recorded as free-text responses. 23 Symptoms derived from the free-text information were either recoded as 1 of the 16 specified symptoms, or otherwise collated into a 17th symptom category labeled as other symptoms (eTable 1 in the Supplement ). Patients for whom symptom information was missing (10 patients), not specified (14 patients), or invalid (3 patients) were excluded from analyses (eFigure in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%